The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/jace.13220
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous and Nonaqueous Colloidal Processing of Difficult‐to‐Densify Ceramics: Suspension Rheology and Particle Packing

Abstract: Aqueous and nonaqueous colloidal processing of zirconium diboride (ZrB 2 ) and boron carbide (B 4 C) has been investigated. The aqueous and nonaqueous ZrB 2 and B 4 C suspension formulations have been optimized. The suspensions were cast into green bodies using slip casting. The correlation between the state of dispersion with the rheological properties of the suspensions and the resulting packing density was observed in both aqueous and nonaqueous processing. The attractive interactions between powder particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 49 publications
(69 reference statements)
3
38
0
Order By: Relevance
“…Previous research on aqueous colloidal processing of B 4 C has been limited to slip and tape casting processes [6,7,10,21,22]. Leo et al [6] reported that aqueous slip casting slurries of B 4 C were only stable up to 40 vol.% when using 2.6 m powders and Darvan C-N, an ammonium salt of poly(methacrylic acid) (PMAA), as a dispersant.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research on aqueous colloidal processing of B 4 C has been limited to slip and tape casting processes [6,7,10,21,22]. Leo et al [6] reported that aqueous slip casting slurries of B 4 C were only stable up to 40 vol.% when using 2.6 m powders and Darvan C-N, an ammonium salt of poly(methacrylic acid) (PMAA), as a dispersant.…”
Section: Introductionmentioning
confidence: 99%
“…Leo et al [6] reported that aqueous slip casting slurries of B 4 C were only stable up to 40 vol.% when using 2.6 m powders and Darvan C-N, an ammonium salt of poly(methacrylic acid) (PMAA), as a dispersant. As stated previously, higher solids loading must be used in a direct writing approach to achieve the desired rheological properties and higher green body packing densities [6,17].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations